Terminally-crosslinked poly(ether sulfone) block copolymer, as a highly selective and stable polymer electrolyte membrane for DMFC applications - Thankamony, Roshni Lilly; Won, Mihee; Kim, Tae-Hyun (International journal of hydrogen energy, 2013)
The terminally-crosslinked sulfonated poly(ether sulfone) block copolymer (SPES-b) was developed for use as a proton exchange membrane in DMFC applications. The properties of the membrane prepared from SPES-b were compared with those of its non-crosslinked counterpart (SPES-bn) and Nafion®-117. The membrane displayed a well-defined morphology due to phase separation between the hydrophobic and hydrophilic ionic units in the SPES-b block copolymer. The terminally-crosslinked SPES-b membrane yielded a high proton conductivity of 0.09 S/cm and a low methanol permeability of 5.3 × 10−8 cm2/s at 20 °C, and the membrane displayed excellent dimensional, mechanical, hydrolytic, and oxidative stabilities. [Display omitted] ► Terminally-crosslinked sulfonated poly(ether sulfone) was prepared. ► High conductivity with low methanol permeability was obtained. ► Dimensional, mechanical, and oxidative stabilities were achieved.